Qualidade física e sensorial de cultivares de coffea arabica L. em diferentes ambientes e métodos de processamento - Alixandre, Fabiano Tristao (2022)
The objective of this work was to evaluate the effects of different cultivars of arabica coffee, at three altitudes (750m, 850m and 1000m) and two processing methods, on the attributes related to the sensory quality of the beverage and the size of the coffee beans. The experiment was carried out in a randomized block design with four replications, in a subplot scheme, with the plots composed of ten cultivars (Catucaí 785/15, Catucaí 2 SL, Catucai 24/137, Catuaí IAC 44, Catiguá MG2, IPR 103, Tupi 1669-33, Arara, Japi and Acauã); and the subplots by two processes, pulped and natural cherry. The harvest was performed manually, harvesting the ripe fruits in a sieve. The coffees were processed by the natural method and pulped cherry. Drying was carried out in a covered suspended terrace, according to the research recommendations for the production of specialty coffees, until the beans reached 11% ± 1 moisture. The following evaluations were carried out: sensory analysis of the beverage according to the SCA methodology (SCA, 2022), analysis of grain sieves according to the Official Brazilian Coffee Classification Protocol (BRASIL, 2003). The results allow us to conclude that all cultivars have potential for the production of specialty coffees, for the processing methods and altitudes evaluated. The elevation of altitude has a positive effect on the intensity of the final drink note of the cultivars for the pulped and natural processing methods. The cultivars showed variations in the intensity of the final beverage grade according to altitude and processing method, demonstrating the existence of genetic variability between cultivars in relation to the potential for sensory beverage quality. The group of cultivars of yellow colored fruit, presented average of the final grades of beverages superior to the group of cultivars of red colored fruit in all environments evaluated for the pulped processing, while for the natural processing it was higher in the altitudes of 750m and 1000m. The group of cultivars moderately resistant to rust presented averages of final beverage grades of pulped cherry coffees higher than cultivars susceptible to rust, at altitudes of 750m and 1000m. For natural processing, the averages of the final beverage grades of the group of cultivars moderately resistant to rust were higher than the group of cultivars susceptible at an altitude of 750m and lower than the group of cultivars highly resistant to rust at an altitude of 850m. The groups of cultivars, Catucai, Híbrido do Timor and Sarchimor presented higher averages of the final notes of beverages of pulped cherry coffees in relation to the Catuaí group, at 1000m altitude. For natural processing, the Sarchimor group was superior to the other treatments at an altitude of 750m and at an altitude of 1000 meters it was superior to the Híbrido do Timor. There are variations among the cultivars in relation to the potential for the production of coarse sieve coffees 17 above, in the different environments and processing methods evaluated. Key words: Altitude; specialty coffees; Processing; varieties